Evaluation of the Practicum for Teaching Degrees from the Students’ Perspective - Michelle Mendoza-Lira; Carmen Gloria Covarrubias-Apablaza (Revista Electrónica Educare)
The Practicum –understood not only as external practices developed by future teachers in schools, but also as the tutorials, seminars and projects done at the University–, is an essential component of initial teacher training. Given the importance of this topic, this paper includes the results obtained in a trans-sectional quantitative descriptive study focused on learning how sampled students from the Primary Teaching and Preschool Teaching Degree Programs from a public university in Madrid evaluate the organization of Practicums I and II, and the support they received from related personnel from the University and the education institution where the practicums took place. A questionnaire was designed to obtain this information from students from these programs and was answered by 426 students. To validate the questionnaire, the Lawshe’s formula was used, which establishes a Content Validity Index (CVI) of 0.62, with ten expert judges for agreement not to be reached by chance. In addition, the information provided by the sample was coded in a database for further processing with SPSS 15.0. Using this software, descriptive analyzes were performed to determine the distribution of the sample in each of the variables defined in this study. Finally, results showed a clear tendency to perceive the training institution (the University) and its most representative agent (tutor) as insufficient to meet the demands for emotional, professional and pedagogical support. On the contrary, centers where practicum is conducted and collaborating teachers are seen not only as the main sources of orientation and guidance during the Practicum, but also as references in the acquisition and development of professional competences.